Bidding with Securities: Comment - Che, Yeon-Koo; Kim, Jinwoo (American Economic Review, 2010)
Peter DeMarzo, Ilan Kremer, and Andrzej Skrzypacz (2005) analyzed auctions in which bidders compete in securities. They show that a steeper security leads to a higher expected revenue for the seller, and also use this to establish the revenue ranking between standard auctions. In this comment, we obtain the opposite results to DKS's by assuming that a higher return requires a higher investment cost. Given this latter assumption, steeper securities are more vulnerable to adverse selection, and may yield lower expected revenue, than flatter ones. (JEL D44)